2014
DOI: 10.1172/jci71104
|View full text |Cite
|
Sign up to set email alerts
|

Sustained activation of SMAD3/SMAD4 by FOXM1 promotes TGF-β–dependent cancer metastasis

Abstract: A key feature of TGF-β signaling activation in cancer cells is the sustained activation of SMAD complexes in the nucleus; however, the drivers of SMAD activation are poorly defined. Here, using human and mouse breast cancer cell lines, we found that oncogene forkhead box M1 (FOXM1) interacts with SMAD3 to sustain activation of the SMAD3/SMAD4 complex in the nucleus. FOXM1 prevented the E3 ubiquitin-protein ligase transcriptional intermediary factor 1 γ (TIF1γ) from binding SMAD3 and monoubiquitinating SMAD4, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
145
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(149 citation statements)
references
References 38 publications
4
145
0
Order By: Relevance
“…We and others have proposed that the tumor-suppressive function of TIF1g could result from its capacity to inhibit TGFb-induced epithelial-to-mesenchymal transition (EMT; refs. 17,26,30,31). However, we have also demonstrated in a transgenic mouse model of pancreatic cancer that the regulation of EMT by TIF1g could not fully explain its tumorsuppressive effect (30), thus indicating that TIF1g was able to regulate other oncosuppressive biologic functions.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We and others have proposed that the tumor-suppressive function of TIF1g could result from its capacity to inhibit TGFb-induced epithelial-to-mesenchymal transition (EMT; refs. 17,26,30,31). However, we have also demonstrated in a transgenic mouse model of pancreatic cancer that the regulation of EMT by TIF1g could not fully explain its tumorsuppressive effect (30), thus indicating that TIF1g was able to regulate other oncosuppressive biologic functions.…”
Section: Introductionmentioning
confidence: 78%
“…At the molecular level, TIF1g is involved in chromatin remodeling and subsequent transcription modulation (3,7,10,13,14). Depending on the cellular context, TIF1g has been described as a potent modulator of the TGFb, acting either as a negative regulator (5,14,(15)(16)(17) or a positive regulator of the pathway (12,13,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xue et al (17) confirmed that the TGF-β1-mediated Smad signaling pathway is involved in tumor recurrence and metastasis. Lang et al (14) demonstrated that TGF-β1 participates in the recurrence and metastasis of breast cancer via urokinase type plasminogen activator (uPA) and plasminogen activator inhibitor (PAI-1) activation.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, it was suggested that SMAD4 is a direct target of miR-574-3p and the associated genes CDKN1A, CDKN2B as well as ID3 were strongly suppressed by miR-574-3p transfection. SMAD4 is often mutated in numerous cancers and it acts as a tumor suppressor that is involved in the regulation of the TGF-β signal transduction pathway, which negatively regulates growth of epithelial cells and the extracellular matrix (28)(29)(30)(31). Therefore, the inhibition of SMAD4 and its downstream proteins may be an important part of the mechanism of miR-574-3p in osteosarcoma.…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 99%